Statement by the Managing Director on the Work Program of the Executive Board : Executive Board Meeting. (Policy Papers; Policy Paper ;, 2016)
The Managing Director's Global Policy Agenda (GPA) presented to the International Monetary and Financial Committee (IMFC) in April called on member countries to reinforce their commitment to strong, sustainable, inclusive, job-rich, and more balanced global growth and to employ a three-pronged approach with monetary, fiscal, and structural actions (Figure 1). The global economy has been impaired by growth that has been too slow for too long, but it can get back on a stronger and safer track with a more forceful and balanced policy mix. Building on the approach of being agile, integrated, and member-focused, the GPA outlined how the Fund would support members in crafting a better policy mix toward durable global growth. The Fund would assist by clarifying the contours of available policy space, providing more tailored financial support and capacity development, and continuing to address new challenges.